Effect of N2 Jet on Si Electrode Surface in Dielectric Barrier Discharge. Issue 2 (February 2020) - Wang, Changquan
Abstract: In order to investigate the effect of discharge gas jet on electrode surface, some dielectric barrier discharge (DBD) experiments were carried out on a laboratory-built DBD system using monocrystalline silicon (Si) electrode in air with or without N2 jet. The effects of N2 jet on Si electrode surface are analyzed by means of field emission scanning electron microscope (FESEM) and energy dispersive X-ray spectroscopy (EDS) attached to FESEM. The results show that Si electrode surface roughness and oxidation with N2 jet are increased more than without N2 jet. It can be used for texturing solar cells surface to improve power conversion efficiency.